Pengembangan Buku Petunjuk Praktikum IPA Berbasis Learning Cycle Bagi Siswa Kelas IV Sekolah Dasar - Faizal Chan; Hendra Budiono (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2019)
The purpose of this study is to produce a science learning manual based on a learning cycle for grade IV students of valid, practical and effective elementary school. The test subjects in this research were grade IV students of SDN 131 / IV Jambi City. This research uses the type of Research and Development (research and development), adopts the ADDIE development model with stages of analysis, design, develop, implementation, and evaluation. The due diligence includes the level of validity and practicality. Data collection instruments in this research development are validity and practicality instruments. The data in this study are quantitative and qualitative data. Quantitative data in the form of the results of the validation of the science practical manual. Qualitative data in the form of teacher and student responses to the developed practical guide. This research resulted in a science learning manual based on a learning cycle with the validity of the material included in the valid category with an average of 3.41, the validity of the display included a very valid category with an average of 3.52. The practicality level of the teacher and student response questionnaire was included in the practical category with an average of 78.75%. Based on the results of the study it can be concluded that the development of science instruction manuals based on leraning cycles for grade IV elementary school students is in the valid and practical categories. From the results of this study it is hoped that the teacher can design a proaticum manual at another grade level.